국가산림자원조사를 이용한 혼효림의 입지환경 탐색 및 임분수확량 추정 - 정성엽; Seongyeop Jeong; 임종수; Jongsu Yim; 이선정; Sunjung Lee; 송정은; Jungeun Song; 박효근; Hyokeun Park; 이정빈; Jungbin Lee; et al. (한국산림과학회지, 2023)
본 연구는 국가산림자원조사 자료를 활용하여 우리나라 혼효림에 대한 산림 입지조건을 탐색하고 임분의 생장 및 수확량을 추정하기 위하여 수행되었다. 혼효림의 생장은 흉고직경, 수고, 흉고단면적을 변수로 하는 Chapman-Richards 모델을 적용하여 식을 도출하였으며, 수확량은 흉고단면적, 지위지수, 임령, 입목밀도 등의 인자를 단계적회귀분석 적용으로 회귀식을 도출하였다. 국내 혼효림은 다양한 입지에 생육하고 있었는데, 기후대별로는 온대중부권역에 과반수 이상이 분포하고 있었으며, 해발고별로는 101~400 m 지역에 약 62%가 분포하는 것으로 나타났다. 임령을 설명변수로 하는 혼효림 생장모형의 적합도(FI)는 흉고직경 0.32, 수고 0.22, 흉고단면적 0.18로 도출되어, 다소 낮은 적합도 값을 갖는 것으로 나타났다. 그러나 추정식의 실측치와 추정치 간의 관계 그래프 및 잔차 등을 고려할 때, 임령을 설명변수로 이용하는 추정모형의 사용은 특별한 문제가 없을 것으로 판단되었다. 혼효림의 수확모형은 여러 생장인자 중 흉고단면적(BA), 지위지수(SI), 임령(Age)이 단계적으로 투입되는 회귀식 Stand volume = - 162.6859+6.3434·BA+9.9214·SI+0.7271·Age 이 도출되었으며, 식의 설명력 (R 2 )은 약 96% 였다. 앞서 도출된 최적의 생장 및 수확모형을 이용하여 임시 임분수확표가 만들어 졌다. 또한 임시 임분수확표 자료를 활용하여 혼효림의 재적수확최대벌기령을 도출하였다. This study was established to investigate the site environment of mixed forests in Korea and to estimate the growth and yield of stands using national forest resources inventory data. The growth of mixed forests was derived by applying the Chapman-Richards model with diameter at breast height (DBH), height, and cross-sectional area at breast height (BA), and the yield of mixed forests was derived by applying stepwise regression analysis with factors such as cross-sectional area at breast height, site index (SI), age, and standing tree density per ha. Mixed forests were found to be growing in various locations. By climate zone, more than half of them were distributed in the temperate central region. By altitude, about 62% were distributed at 101-400 m. The fitness indexes (FI) for the growth model of mixed forests, which is the independent variable of stand age, were 0.32 for the DBH estimation, 0.22 for the height estimation, and 0.18 for the basal area at breast height estimation, which were somewhat low. However, considering the graph and residual between the estimated and measured values of the estimation equation, the use of this estimation model is not expected to cause any particular problems. The yield prediction model of mixed forests was derived as follows: Stand volume = - 162.6859+6.3434·BA+9.9214·SI+0.7271·Age, which is a step- by-step input of basal area at breast height (BA), site index (SI), and age among several growth factors, and the determination coefficient (R 2 ) of the equation was about 96%. Using our optimal growth and yield prediction model, a makeshift stand yield table was created. This table of mixed forests was also used to derive the rotation of the highest production in volume.